Votive inscriptions in Linear A - Tomas, Helena (2002)
Paper discusses votive inscriptions in the Bronze Age Cretan Linear A script still undeciphered. Votive inscriptions on libation tablets, votive cups, a ladle, a figurine, axes, silver pins and a golden ring, are continious texts and should offer some ideas on the sintax of the language as well as of the ritual cotext in which they were used.
Projekt MZOS
ENG